2017
DOI: 10.1080/13510002.2017.1322750
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid protects againstN-nitrosodimethylamine-induced redox imbalance in testes of rats

Abstract: Objectives: N-nitrosodimethylamine (NDMA) is known to elicit carcinogenic activity in the liver and kidney of animals. There is a dearth of information of its effect in testis. This study evaluated the protective role of betulinic acid (BA) against NDMA-induced redox imbalance in testes of rats. Methodology: Twenty-four male rats were assigned into four groups and treated with normal saline, BA, NDMA and [BA+NDMA]. BA (25 mg/kg) was given for 14 days, while NDMA (5 mg/kg) was given on days 7 and 12. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The authors associated the latter observation with the finding that the testosterone levels did not increase. Adeleke and Adaramoye () studied the protective role of betulinic acid on nitrosodimethylamine‐induced redox imbalance in rat testis. They reported that nitrosodimethylamine, a nitrosamine compound, was known for its carcinogenic activity in the liver and kidney of animals; however, the information about the effects on the testis tissue was limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors associated the latter observation with the finding that the testosterone levels did not increase. Adeleke and Adaramoye () studied the protective role of betulinic acid on nitrosodimethylamine‐induced redox imbalance in rat testis. They reported that nitrosodimethylamine, a nitrosamine compound, was known for its carcinogenic activity in the liver and kidney of animals; however, the information about the effects on the testis tissue was limited.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that nitrosodimethylamine, a nitrosamine compound, was known for its carcinogenic activity in the liver and kidney of animals; however, the information about the effects on the testis tissue was limited. Adeleke and Adaramoye () demonstrated that the administration of nitrosodimethylamine significantly reduced the sperm density, motility and live‐dead ratio by 57%, 36% and 37%, respectively, and increased the total abnormal sperm rate by 56% while testicular TBARS and total cholesterol levels were increased. The authors determined that betulinic acid displayed protective effects against nitrosodimethylamine‐induced redox imbalance via the activation of the antioxidative pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These processes results in extreme oxidative stress and production of reactive oxygen species (ROS) that further contributes to hepatocyte damage and necrosis. Furthermore, NDMA decreases catalase and glutathione peroxidase, the major antioxidant enzymes present in the liver 7981 . We have observed that NDMA treatment dramatically decreases serum and liver concentrations of ascorbic acid, another major antioxidant 10 .…”
Section: Events Involved In the Pathogenesis Of Ndma Induced Hepatic mentioning
confidence: 97%
“…We have earlier reported that BA ameliorated NDMA-induced adverse effects on the activities of UDPGT, AnH, and AmD in the testicular organs of rats. [54] Histopathology revealed severe periportal cell infiltration by mononuclear cells, periportal fibroplasia (fibrosis), and few foci of necrosis in hepatic tissues, while cortical degeneration, foci tubular necrosis, and tubular deposition of proteinaceous materials in renal tissues of NDMAadministered rats were observed. The infiltration of mononuclear cells into the hepatocytes and deposition of proteinaceous materials in the renal tubular lumen may be due to changes in structural integrity and lipid-protein interaction in biological membranes of these tissues caused by NDMA.…”
Section: Discussionmentioning
confidence: 94%